Pro JavaFX 9 A Definitive Guide to Building Desktop, Mobile, and Embedded Java Clients - Vos, Johan (Apress, 2018)
Use the JavaFX platform to create rich-client Java applications and discover how you can use this powerful Java-based UI platform, which is capable of handling large-scale data-driven business applications for PC as well as mobile and embedded devices. The expert authors cover the new more modular JavaFX 9 APIs, development tools, and best practices and provide code examples that explore the exciting new features provided with JavaFX 9, part of Oracle's new Java 9 release.Pro JavaFX 9: A Definitive Guide to Building Desktop, Mobile, and Embedded Java Clients also contains engaging tutorials that cover virtually every facet of JavaFX development and reference materials on JavaFX that augment the JavaFX API documentation. New material in this edition includes JavaFX UI controls and CSS APIs for modularization. Additionally, there is coverage of the Shader DSL for JavaFX that allows you to generate Shaders for OpenGL and Direct3D. After reading and using this book, you'll have the knowledge to give you an edge in your next JavaFX-based project. You will: Create a user interface in JavaFX Use SceneBuilder to create a user interface Build dynamic UI layouts in JavaFX and using the JavaFX UI controls Create charts in JavaFX Use the media classes, including JavaFX 3D Design and deploy for embedded, mobile and tablet Leverage JavaFX languages and markup .